PERENCANAAN KEBIJAKAN PENATAAN BANGUNAN DAN LINGKUNGAN PADA KAWASAN WISATA SARANGAN - Jamiatun Juliana; Singgih Manggalou (Journal Publicuho, 2024)
The planning of building and environmental management policies for the Sarangan Tourism Area was carried out through the RTBL program, which provides a guideline for organizing areas that do not yet comply with regulations. This study examined how the Dinas Perumahan Rakyat, Kawasan Permukiman, and dan Cipta Karya Provinsi Jawa Timur planned the RTBL policy using a descriptive qualitative approach based on Handoko’s (2003) planning theory. The results showed that the planning process was well-executed, with clear and measurable goals focused on reorganizing the area’s buildings and environment to support sustainable development. Strategies were carefully designed using SWOT analysis to ensure the policies were effective and aligned with the area’s needs while adhering to national and regional regulations, such as PERMEN-PUPR No. 06/PRT/M/2007. Projects and programs were implemented on schedule and followed proper procedures, using a combination of a top-down approach and limited bottom-up input. Funding was allocated through supervision and development planning forums, ensuring the program met all required standards.